Pengaruh Komunikasi Interpersonal Orangtua dengan Anak Terhadap Kenakalan Remaja Pada Siswa : Studi Kasus SMP Negeri 2 Salapian - Fedy Komar (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study is to study and empirically prove the presence or absence of influence on the quality of interpersonal communication with children on juvenile delinquency instudents. The sampling method is Random Sampling, with a large sample of 28 people. The method used in this research is descriptive method, Quantitative data analysis method is the method of analysis used in research. The data to be analyzed in this study are data from the variables of interpersonal communication of parents with children (as dependent variables) and juvenile delinquency variables (as independent variables). This analytical technique used a value scale: 3.26-4.00 (excellent category, 2.51-3.25 (good/high category), 1.76-2.50 (pretty good category/high enough), 1.00-1.75 (less good/low category), From the results of data processing, it was concluded that: Parental interpersonal communication with children falls into the category of good or high with an average score of 3.07. Juvenile delinquency in students falls into the low category, with an average score of 1.03. From the results of the calculation obtained the correlation coefficient r = 0.32 (moderate positive correlation). through testing using the t Distribution, obtained; th = 1,76, tt(1-1/2) =1,701, with the provision of acceptance Ho if = –t(1-1/2 ).It turns out that through calculation th is not amongt(1-1/2) dan t(1-1/2). (-1,701 and 1,701), Then the hypothesis upheld in this study is acceptable. To find the magnitude of influence, the formula of the coefficient of determination isused. From the results of the calculation obtained a coefficient of determination of 0.106 which means the magnitude of the influence of 1.12%. From the results of the above hypothesis testing it can be concluded that the factor of parental communication with children is one of the factors that affect the level of juvenile delinquency, with an influence rate of about 1.12%.